The 'war on terror' and the battle for the definition of torture. (March 2016) - Barnes, Jamal
The use of torture by the Bush administration has raised important questions regarding the strength of the torture taboo. Did US torture signal a regress of the torture prohibition? This article examines the attempts by the United States to re-define torture to better reflect its interests. However, rather than seeing this as a case of norm regression, I show how the United States failed in its revisionist attempts to legitimise its interpretation of torture in international society. The torture taboo remained resilient to US challenges, demonstrating not only the difficulty of norm revisionism but also the robustness of the torture taboo.